Examining inclusive practices in Nicaraguan schools - Delkamiller, Julie; Swain, Kristine; Leader-Janssen, Elizabeth M.; Ritzman, Mitzi J (Social Welfare: Interdisciplinary Approach, 2013)
The purpose of this study was to examine Nicaraguan teachers’ efficacy for inclusive practices and current teaching practices in Nicaraguan schools as the first step in developing a special education training program. Sixty-one teachers in 15 schools completed the Teacher Efficacy of Inclusive Practice (TEIP) survey to determine their confidence in inclusive practices, collaboration and dealing with disruptive behaviors. Classroom observations were also completed to examine the environment, teaching/learning strategies, student behaviors, learning materials, and time distribution in the classroom. Results from the TEIP indicated Nicaraguan teachers were highly efficacious in inclusive practices. The survey and observation data collected provided a baseline to develop goals and objectives for a two-year special education training.